(untitled) (Nigerian Journal of Technology, 2015)
Load Loss Factor (LLF) is a function of the estimate of the losses between the grid supply point and the consumers. It varies with voltage levels and types of consumers (such as domestic, industrial or commercial). This technical note compares the accuracy of LLF derived from exact daily and seasonal variation in demand and estimated values from the system load factor (LF). http://dx.doi.org/10.4314/njt.v34i3.17